1984
DOI: 10.1002/j.1460-2075.1984.tb01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Laminin is induced in astrocytes of adult brain by injury.

Abstract: Laminin is a high mol. wt. non-collagenous matrix glycoprotein, confined in adult tissues to basement membranes. In normal rat brain we found laminin mainly in vessel walls but, after injury, induced by stereotaxic injection of a neurotoxin, laminin immunoreactivity appeared also in reactive astrocytes, which are characteristically positive for the glial fibrillary acidic protein (GFAP). Laminin was first detected in GFAPimmunoreactive glial cells 24 h after injury. Four days later the majority of reactive ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
2
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(129 citation statements)
references
References 36 publications
10
116
2
1
Order By: Relevance
“…Post-natal rats were anaesthetised with tribromoethanol, the brains fixed with 0.4% BQ in PBS for 2 min using transcardial perfusion, and then prepared for cryostat sections in the sagittal plane. Light microscopic immunocytochemistryfor laninin, vimentin, GFAP andfibronectin The cryostat sections were air-dried for 1 h before rinsing them in PBS followed by dehydration and rehydration as described (Liesi et al, 1984a). The sections were incubated ovemight at +40C with nonral sheep serum diluted 1/30.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-natal rats were anaesthetised with tribromoethanol, the brains fixed with 0.4% BQ in PBS for 2 min using transcardial perfusion, and then prepared for cryostat sections in the sagittal plane. Light microscopic immunocytochemistryfor laninin, vimentin, GFAP andfibronectin The cryostat sections were air-dried for 1 h before rinsing them in PBS followed by dehydration and rehydration as described (Liesi et al, 1984a). The sections were incubated ovemight at +40C with nonral sheep serum diluted 1/30.…”
Section: Methodsmentioning
confidence: 99%
“…Second, although absent from adult brain glia, laminin is transiently produced by astrocytes both in culture and in vivo after brain injury (Liesi et al, 1984a). Third, when presented as a substrate molecule, laminin promotes spreading and neurite outgrowth of both peripheral and central neurons (Baron-Van Evercooren et al, 1982;Rogers et al, 1983;Manthorpe et al, 1983;Liesi et al, 1984b;Edgar et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] In many scaffold-based cultures, the scaffold introduces foreign ECM to the microenvironment, which can potentially modify cell behavior and mask disease-related changes in the culture model. In the spheroids of this work, the cells produced all of the ECM.…”
Section: Versatile Culturementioning
confidence: 99%
“…Specifically, reactive astrogliosis is denoted by increased immunoreactivity of glial fibrillary acid protein (GFAP), which is a distinct cellular marker of astrocytes. 14,48,[71][72][73][74]111 It has been demonstrated that reactive adult astrocytes upregulate the production of laminin and neurotrophin C. 75,76 In addition to the endogenously present myelinassociated neurite growth inhibitory constitutents, reactive astrocytes form an astroglial scar that acts as a physical and/or chemical barrier to axonal regeneration. 8,35,72,77,78 Proximity to the lesion epicentre determines whether the reactive glial environment will be growth supportive or inhibitory.…”
Section: Experimental Modelsmentioning
confidence: 99%